Multivariate analysis of psychological factors related to adolescent smoking - Mohammadpoor Asl A.; Fakhari A.; Rostami F.; Tabatabaee S.M. (Payesh, 2006)
Objective (s): The purpose of this paper is to determine the prevalence and psychological factors of smoking among 1785 students at 30 high schools in Tabriz. Methods: Each student completed a self-administered questionnaire. The intention was to obtain information on smoking, self-esteem, and attitude toward smoking as well as demographic information. Respondents were classified into three categories of never smoker, occasional smoker and regular smoker. Multivariate logistic regression analysis was used to determine the association between smoking status and the independent variables. Results: The prevalence of ever smoking was 22.6% but only 4.4% of the students were regular smokers. Prevalence was higher among students who had experienced alcohol (OR=J.53) and illicit drugs (OR=9.99). Prevalence was also higher among students who had a positive attitude toward smoking (OR=l .26). Conclusion: Smoking prevention programs for adolescents should be adapted at each stages of smoking. The finding has important public health implications, but further research is required to determine if the association was causal.